Relationship Between Pregnant Women's Knowledge And Attitudes About Pregnancy Exercises And Smooth Normal Delivery Process - Siti Arfah Siregar; Rismaida Saragih (Sekolah Tinggi Ilmu Kesehatan Kesdam IV, Diponegoro Semarang, Indonesia, 2024)
During pregnancy, a mother will experience various changes, both anatomical and physiological. Pregnancy exercise is one of the activities in pregnancy services or prenatal care that aims to prepare and train muscles so that they can be used optimally in normal delivery. Knowledge and attitude are factors in the formation of behavior. The purpose of this study was to identify the relationship between knowledge and attitudes of pregnant women with the implementation of pregnancy exercise. This type of research is quantitative analytic using a cross-sectional design. The time of the study was August 18 - September 3, 2010. The sampling technique was purposive sampling through non-probability sampling of 55 people. Data collection through interviews using structured questionnaires. Data analysis used was univariate and bivariate (chi square, simple logistic regression, and correlation test). The results showed that most pregnant women at the Ciputat Health Center had good knowledge about pregnancy exercise, namely 40 respondents (72.7%), had a positive attitude towards pregnancy exercise, namely 36 respondents (65.5%), and 32 respondents (58.2%) did not do pregnancy exercise. Based on bivariate data analysis, the p Value = 0.037 was obtained, which means there is a relationship between knowledge and the implementation of pregnancy exercises (p <0.05). Significant results were also obtained with a p Value = 0.001, which means there is a relationship between attitude and the implementation of pregnancy exercises (p <0.05). Based on the results of the study, the author suggests increasing health promotion about pregnancy exercises, and holding pregnancy exercise programs for pregnant women.